Clinical Characteristics of Asthma Combined with COPD Feature - Lee, Hea Yon (Yonsei University College of Medicine, 2014)
PURPOSE: In clinical practice, some patients with asthma show incompletely reversible airflow obstruction, resembling chronic obstructive pulmonary disease (COPD). The aim of this study was to analyze this overlap phenotype of asthma with COPD feature. MATERIALS AND METHODS: A total of 256 patients, over the age of 40 years or more with a diagnosis of asthma, based on either 1) positive response to bronchodilator: >200 mL forced expiratory volume in 1 s (FEV(1)) and >12% baseline or 2) positive methacholine or mannitol provocation test, were enrolled. Among the asthma patients, we defined the overlap group with incompletely reversible airflow obstruction [postbronchodilator FEV(1)/forced vital capacity (FVC) <70] at the initial time of admission and continuing airflow obstruction after at least 3 months follow up. We evaluated clinical features, serum eosinophil counts, serum total immunoglobulin (Ig) E with allergy skin prick test, spirometry, methacholine or mannitol provocation challenges and bronchodilator responses, based on their retrospective medical record data. All of the tests mentioned above were performed within one week. RESULTS: The study population was divided into two groups: asthma only (62%, n=159, postbronchodilator FEV(1)/FVC ≥70) and overlap group (38%, n=97, postbronchodilator FEV(1)/FVC <70). The overlap group was older, and contained more males and a higher percentage of current or ex-smokers than the asthma only group. Significantly lower FEV(1) and higher total lung capacity, functional residual capacity, and residual volume were observed in the overlap group. Finally, significantly lower serum eosinophil count and higher IgE were seen in the overlap group. CONCLUSION: Our results showed that the overlap phenotype was older, male asthmatic patients who have a higher lifetime smoking intensity, more atopy and generally worse lung function.